1996
DOI: 10.1006/viro.1996.0320
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simian Immunodeficiency Virus Infectionin Vitroandin Vivoon the Cytokine Production of Isolated Microglia and Peripheral Macrophages from Rhesus Monkey

Abstract: Microglia are the major target for human immunodeficiency virus (HIV) infection within the central nervous system. Because only a few cells are productively infected, it has been suggested that an aberrant cytokine production by this cell population may be an indirect mechanism leading to the development of neurological disorders in HIV-infected patients. Therefore we decided to study the secretion pattern of several interleukins (IL) by microglial cells and peripheral blood macrophages isolated from uninfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 1 publication
1
41
0
Order By: Relevance
“…This is consistent with a previous study in which TNFa immunoreactivity in MVV-infected brain tissues was demonstrated to associate with brain macrophages (Craig et al, 1997). Intrathecal expression of TNFa has also been demonstrated in primate lentivirus infections (Nuovo and Al®eri, 1996;Sopper et al, 1996). Increased transcription of IL-6 mRNA has also been reported in caprine microglial cultures infected with CAEV (Baszler et al, 1994) and in the brains of SIV-infected macaques (Sopper et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with a previous study in which TNFa immunoreactivity in MVV-infected brain tissues was demonstrated to associate with brain macrophages (Craig et al, 1997). Intrathecal expression of TNFa has also been demonstrated in primate lentivirus infections (Nuovo and Al®eri, 1996;Sopper et al, 1996). Increased transcription of IL-6 mRNA has also been reported in caprine microglial cultures infected with CAEV (Baszler et al, 1994) and in the brains of SIV-infected macaques (Sopper et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Intrathecal expression of TNFa has also been demonstrated in primate lentivirus infections (Nuovo and Al®eri, 1996;Sopper et al, 1996). Increased transcription of IL-6 mRNA has also been reported in caprine microglial cultures infected with CAEV (Baszler et al, 1994) and in the brains of SIV-infected macaques (Sopper et al, 1996). Over-expression of IL-6 in the murine CNS has been shown to result in reactive astrocytosis and an increase in rami®ed microglial cells (Fattori et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This last observation gives new insight into mechanisms underlying amyloid plaque formation in the CNS during Alzheimer disease. Microglial cells infected by SIV in vitro can produce more IL-8 than uninfected cultures (Sopper et al, 1996).…”
Section: Chemokine Expression By Cns Cells In Vitromentioning
confidence: 99%